Associations of built environments with spatiotemporal patterns of shared scooter use: A comparison with shared bike use. (September 2022) - Liu, Hung-Chi; Lin, Jen-Jia
Abstract: This article presents a comparative study aimed at clarifying the similarities and differences between scooter sharing service (SSS) and bike sharing service (BSS) uses in terms of the link between built environments and spatiotemporal patterns. The data comprise study observations from the rental records of SSS and BSS in Taipei, Taiwan. These data were analyzed using spectral clustering method and logit models. The comparison results between SSS and BSS suggest that motorized vehicle usage and high usage cost result in SSS uses revealing long travel distances and different associations of built environments with spatiotemporal patterns from BSS uses. The distance-to-transit variables are related to the spatiotemporal patterns of BSS uses but are unrelated to those of SSS. The difference indicates that existing knowledge on BSS is partially inapplicable to SSS and provides valuable information for transport planners in developing cooperation plans among different transport systems in a city. Highlights: Spatiotemporal patterns of SSS use on weekdays are different from those on holidays. Spatiotemporal patterns of SSS use are different from those of BSS use. Spatiotemporal patterns of SSS and BSS uses are associated with different locations. Spatiotemporal patterns of SSS use are associated with built environments. The associations are both similar to and different from those of BSS.